Balancing International Legal Obligations, Human Rights, and National Interests: Indonesia’s Response to Rohingya Refugees in Aceh - Asphianto, Aan; Jaya, Belardo Prasetya Mega; Wicaksono, Agung Satrio; Ashady, Suheflihusnaini; Weku, Robert Lengkong; Anggita, Dila; Risyawan, Alief (LAW REFORM, 2026)
The principle of non-refoulement in international law obliges states to refrain from returning refugees to places where they face persecution. Indonesia, as a state that upholds human rights, has applied this principle in receiving Rohingya refugees who are displaced from their country of origin. Nevertheless, its implementation encounters tensions between international obligations, national interests, and human rights considerations. This study aims to examine how international law influences Indonesia’s response to the Rohingya refugee situation and to analyze the government’s stance in balancing these competing interests. A mixed-method approach is employed, combining empirical research through focus group discussions and interviews with normative analysis of primary and secondary legal materials. The findings indicate that, despite not ratifying the 1951 Refugee Convention, Indonesia continues to adhere to the non-refoulement principle. However, regulatory improvements are necessary, particularly regarding Presidential Regulation No. 125 of 2016, to ensure fulfillment of refugees’ basic rights and adequate financial support, especially in Aceh. In conclusion, Indonesia must adopt prudent legal reforms to strengthen legal certainty, protect refugee rights, and balance international, national, and humanitarian interests effectively. Such measures will also enhance coordination among institutions, improve policy implementation, and promote sustainable humanitarian governance in addressing future refugee challenges comprehensively nationwide.